Process efficiency enhancement of single mixed refrigerant LNG process - Nazreen Begum, Najibullah Khan; Dhiviya, Tinakaran (AIP Publishing, 2025)
Liquefied Natural Gas (LNG) processing is as an energy and cost-intensive process due to the large energy consumption required to liquify the gas. The objective of this study is to enhance the process efficiency of a Single Mixed Refrigerant (SMR) LNG process for a small-scale LNG train with a capacity of 1-2 million tonnes per annum (MTPA). The process efficiency is enhanced by determining the optimal combination of mixed refrigerant composition such as nitrogen, methane, ethane, propane and butane that will minimise the overall energy consumption. The SMR LNG process is modelled and simulated using Aspen Plus. The process efficiency is evaluated using two parameters which are specific power (SP) and coefficient of performance (COP). By enhancing the mixed refrigerant composition of SMR process the results indicate that the specific power (SP) is improved from 0.225 kWh/kg to 0.218 kWh/kg (i.e. improvement about 3.3%). Meanwhile, the coefficient of performance (COP) is improved to 4.22 which indicate about 5% improvement in term of process efficiency enhancement.